Application of Artificial Intelligence in the Insurance Industry: A Case Study of Iran's Basic Health Insurers - Doroudi, Homa; Sami, Mohammad Ali; Heidari, Yasser (Digital Transformation and Administration Innovation, 2026)
The insurance industry is one of the oldest global industries, fundamentally concerned with risk management. With the initiation of the electronic prescription and dispensing plan in Iran, basic health insurers are facing a vast amount of online data, which can increase the risk level in this sector. Analyzing this data requires specialists, selecting the best methods for processing prescriptions, and identifying and preventing novel insurance frauds to meet the needs of insurers in preserving resources and providing quality services to the insured and medical centers. Therefore, this study aims to identify the most significant methods through which Artificial Intelligence (AI) can assist basic health insurers. Through library studies and utilizing a qualitative method with the Delphi technique, 28 effective methods were identified based on the input of 14 selected experts via purposive sampling. Subsequently, the research model and a diagram illustrating the position of AI in the insurance industry for Iran's basic health insurers were developed.